IDENTIFYING LOW CARBON TECHNOLOGY FOR SUSTAINABLE ENERGY DEVELOPMENT IN INDONESIA - Kardono, Kardono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2014)
As a developing country, Indonesia has voluntarily committed to reduce its green-house gases(GHGs) emissions by 26% with its self-financing, or 41% with addition of foreign aids, by year 2020.This target will carry consequences for Indonesia to make an action plan and at the same time tochoose which low carbon technologies (LCTs) are employed in reducing its GHGs. This paper willfocus on introducing LCTs for energy sector of Indonesia. LCTs option for reducing CO2 emissionin Indonesia is suggested for both energy supply and energy demand sides. Energy technology forsupply side is prioritized for clean coal, geothermal and renewable energy technologies includingtechnologies for biomass, hydro, wind and solar. Prioritized energy technology for demand sideis applied to energy efficiency for industries, residential and commercial buildings. Besides, softtechnologies such as energy audit, energy rating and labeling are also proposed. For public bustransportation and taxi, a cleaner fuel of gas as a substitution to fossil fuel or gasoline is highlysuggested to be used. Transport demand management is also proposed to be improved, like usingintelligent transportation system (ITS) and mass rapid transport system (MRTS)